PENGARUH KEPUASAN KERJA TERHADAP PEMBERDAYAAN MELALUI PENGALAMAN KERJA PERUSAHAAN TELEKOMUNIKASI - Erik Wardhana (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
The background of this research examines the effects of job satisfaction and work experience on employee-desire for empowerment. The objectives of this research was analyzed the effect of job satisfaction on empowerment, the effect of job satisfaction on work experience, the effect of work experience on empowerment. A sampling with purposive sampling techniques of two hundred Employee’s in Telecommunication company as the respondents provided the data that were analyzed for this study. Using a sub-set of the sample consisting of was used to test three hypothesized relationships in the model. Data analysis in this research was used Structural Equation Model (SEM) to test the independent variables influence the dependent variable. The findings help to explain failures in organizational efforts to empower workers by demonstrating the critical role of job satisfaction and work experience behaviors in heightening employee-desire for empowerment.